Asteroids [ deadly impact - Parmee, Nina; Weirench, Eitan (National Geographic : Distributed by Home Warner Video, 2003)
Every year, millons of these "stray bullets" streak through the skies, and tons of small meteorites strike our planet. Some 65 millons yeaes ago, dinausors were wiped off the face of the earth-in what many believes was the aftermath of a massive cosmic collision.could something like this happen again?Scientists believe that the impact of an asteroids only a mile wide would be globally catastrophic.join renowned geologist Eugene Shoemaker and his wife, Carolyn, who together have remapped the heavens with their discoveries of more than 30 comets and hundreds of asteroids.now that we know what's out there, how can we defend ourselves?